Rheology of polymeric systems : principles and applications - Carreau, Pierre J.; De Kee, D.; Chhabra, R. P. (Hanser Publishers, 2021)
"Rheology is applied extensively in polymer, chemical, food processing, and related industries. This book combines the basic concepts and applications by presenting a balanced overview of the principles. With simplified analysis of complex problems, the textbook format provides easy understanding for both students and practicing professionals. There is no competing book with such a wide scope, including unique topics such as non-Fickian diffusion, flows about particles, and liquid mixing. The second edition is abundantly updated throughout. Highlights include yield stress measurements, non-Fickian diffusion and rheology of polymer nanocomposites, new results based on CFD simulations, and much more"--Print version, page 4 of cover.
Description based upon print version of record.
Keywords: Polymers -- Rheology -- Textbooks.; Polymers -- Rheology.; elektronické knihy; electronic books